Hydrogenous mineral neoformations in Tomsk water intake facility from underground sources; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Dutova E. M. Ekaterina Matveevna; Vologdina I.; Pokrovsky D.; Nalivayko N. G. Nina Grigorievna; Kuzevanov K. I. Konstantin Ivanovich; Pokrovsky V. D. Vitaly Dmitrievich (Hydrogeochemistry, 2016)
Title screen